Analisis Komunikasi Petani Karet Pola Swadaya di Kecamatan XIII Koto Kampar Kabupaten Kampar - Rusdayani, Fina; Yulida, Roza; Sayamar, Eri (Politeknik Pertanian Negeri Payakumbuh, 2019)
This research aims to determine the internal characteristics and external characteristics of rubber farmers in self-help patterns and the communication process in Subdistrict XIII Koto Kampar, Kampar District.. Based on data on the area of ​​rubber plantations and the amount of rubber production in Riau Province has decreased in the last four years. This is caused by various factors, one of which is due to farmers' communication processes that are running poorly or not as expected. Therefore, it is necessary to analyze the internal and external characteristics of independent smallholder rubber farmers and the communication process through the elements of communication using survey methods, sample selection with purposive sampling method and Likert scale analysis tools and descriptive analysis. Based on Likert scale analysis, internal characteristics and external characteristics of rubber farmers in District XIII Koto Kampar, Kampar Regency are in the moderate category (quite good). The communication process in this study is seen from the elements of communication, namely communicators, messages, media, communicants, effects, feedback, place and time dimensions